2018
DOI: 10.1007/s10120-018-0864-4
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of laparoscopic total gastrectomy for clinical stage I gastric cancer: a prospective multi-center phase II clinical trial, KLASS 03

Abstract: LTG performed by experienced surgeons showed acceptable postoperative morbidity and mortality for patients with clinical stage I gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
79
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 25 publications
7
79
2
6
Order By: Relevance
“…The South Korean KLASS 03 feasibility study on MITG on patients with stage I proximal gastric cancer has found postoperative morbidity rates of 20.6% with grade III or higher of 9.4% and a mortality of 0.6% [28].…”
Section: Discussionmentioning
confidence: 99%
“…The South Korean KLASS 03 feasibility study on MITG on patients with stage I proximal gastric cancer has found postoperative morbidity rates of 20.6% with grade III or higher of 9.4% and a mortality of 0.6% [28].…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic leakage is the most common and serious PCs after gastrectomy. According to a recent large-scare cohort study and multicenter phase II studies, the prevalence of esophagojejunal anastomotic leakage (EJAL) for laparoscopic total gastrectomy range from 1.7 to 5.7% [27][28][29]. In this study, the incidence of EJAL was 11.4% (95% CI 5.6-17.2%), higher than data reported by former research.…”
Section: Discussionmentioning
confidence: 48%
“…The anastomosis-related complications included three cases of anastomotic leakage at the EJ site and 2 cases of stricture in both groups, respectively. Recently, two RCTs investigating only TLTG (and not OTG) were reported [ 27 , 28 ]. The Chinese Laparoscopic Gastrointestinal Surgery Study (CLASS) Group reported the safety and feasibility of laparoscopic spleen-preserving No.…”
Section: Discussionmentioning
confidence: 99%
“…cancer to determine the safety and feasibility of LTG [27]. The short-term results of the safety and feasibility of LTG (KLASS-03 trial, 179 patients) were reported [27]. [25].…”
mentioning
confidence: 99%